1993
DOI: 10.1002/ijc.2910550430
|View full text |Cite
|
Sign up to set email alerts
|

Nerve growth factor effects on human and mouse melanoma cell invasion and heparanase production

Abstract: The role of growth factor networks in regulating the progression of human melanocytes towards tumorigenicity and ultimately the malignant phenotype is poorly understood. In particular, the autocrine and paracrine influences that modulate cellular invasion and extracellular matrix degradative enzymes of melanoma cells remain undefined at the molecular level. We report here that nerve growth factor (NGF) can modify some metastasis-associated cellular properties of human and mouse melanoma cells. Treatment of ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
96
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 84 publications
(98 citation statements)
references
References 24 publications
2
96
0
Order By: Relevance
“…B16B15b or 70W melanoma cells were used as a source of heparanase activity (7,27). We have previously shown that 1) these brainmetastatic clones possess higher heparanase content than their respective murine (B16F1) or human (MeWo) parental counterparts, and 2) the heparanase activity is indistinguishable in these two cellular sources by the two heparanase assays used in the present studies (7,27,29). Briefly, subconfluent cells were harvested and solubilized in 50 mM Tris-HCl, pH 7.5, 0.05% (w/v) sodium azide, 0.5% (v/v) Triton X-100 for 30 min at 4°C.…”
mentioning
confidence: 67%
See 4 more Smart Citations
“…B16B15b or 70W melanoma cells were used as a source of heparanase activity (7,27). We have previously shown that 1) these brainmetastatic clones possess higher heparanase content than their respective murine (B16F1) or human (MeWo) parental counterparts, and 2) the heparanase activity is indistinguishable in these two cellular sources by the two heparanase assays used in the present studies (7,27,29). Briefly, subconfluent cells were harvested and solubilized in 50 mM Tris-HCl, pH 7.5, 0.05% (w/v) sodium azide, 0.5% (v/v) Triton X-100 for 30 min at 4°C.…”
mentioning
confidence: 67%
“…Alternatively, heparanase activity was determined by high speed gel permeation chromatography (38) with some modifications (27). B16B15b or 70W melanoma cells were used as a source of heparanase activity (7,27). We have previously shown that 1) these brainmetastatic clones possess higher heparanase content than their respective murine (B16F1) or human (MeWo) parental counterparts, and 2) the heparanase activity is indistinguishable in these two cellular sources by the two heparanase assays used in the present studies (7,27,29).…”
mentioning
confidence: 91%
See 3 more Smart Citations